2022
DOI: 10.3389/fmicb.2022.985283
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of gut microbiota toward renal function in sepsis

Abstract: Sepsis most often involves the kidney and is one of the most common causes of acute kidney injury. The prevalence of septic acute kidney injury has increased significantly in recent years. The gut microbiota plays an important role in sepsis. It interacts with the kidney in a complex and multifactorial process, which is not fully understood. Sepsis may lead to gut microbiota alteration, orchestrate gut mucosal injury, and cause gut barrier failure, which further alters the host immunological and metabolic home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…Studies have shown that dysbiosis of the gut microbiota could exacerbate AKI [22,23]. Therefore, we utilized the 16S rRNA technique to examine the gut flora of each group of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dysbiosis of the gut microbiota could exacerbate AKI [22,23]. Therefore, we utilized the 16S rRNA technique to examine the gut flora of each group of mice.…”
Section: Discussionmentioning
confidence: 99%
“…and Candida albicans [26,27]. This combination of increased permeability and overgrowth of potentially harmful pathogens at the mucosal surface results in a ‘leaky gut’, in which toxins and bacteria penetrate the systemic circulation, promote pathological systemic inflammation, and drives multiorgan dysfunction as seen in the lungs [28], kidney [29] and the brain [30 ▪ ]. Prevention or restoration of the intestinal microbial ecosystems might, therefore, be key in breaking the vicious circle that leads to the immune dysregulation and organ dysfunction that is the hallmark of sepsis.…”
Section: Microbiota-mediated Immunomodulation and Sepsis Pathophysiologymentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common complication of sepsis, and sepsis-associated AKI (SA-AKI) increases the risk of patient mortality (Peng et al, 2014). Existing research suggests that the gut microbiota is involved in the occurrence and progression of SA-AKI (Zhang et al, 2018;Chavez-Iñiguez et al, 2022;Xu et al, 2022). Meijers et al proposed the concept of the "gut-kidney axis" in 2011; subsequently, Pahl et al refined the theory (Meijers and Evenepoel, 2011;Pahl and Vaziri, 2015).…”
Section: Introductionmentioning
confidence: 99%